Survival Benefits of Simple Versus Extended Cholecystectomy and Lymphadenectomy for Patients With T2 Gallbladder Cancer: A Propensity-Matched Population-Based Study (2010 to 2015) - Zhang, Wei; Huang, Zhangkan; Wang, Wen-er; Che, Xu (Frontiers in Oncology, 2021)
Objective: This article aim to evaluate the survival benefits of simple cholecystectomy, extended cholecystectomy, as well as scope regional lymphadenectomy for T2 gallbladder cancer (GBC) patients. Methods: We identified eligible patients from the Surveillance, Epidemiology, and End Results database. The confounding factors were controlled via propensity score matching. The log-rank test was utilized to compare overall survival. The multivariate Cox regression was then used to determine risk factors. Results: Overall, data from 1009 patients were obtained. The median overall survival (OS) of 915 patients that underwent simple cholecystectomy was 15 months; the median OS of 94 patients that underwent extended cholecystectomy was 17 months. There were no significant differences before and after propensity score matching (p = 0.542 and p = 0.258). The patients who received regional lymphadenectomy did show significant survival benefit, compared to those who did not received regional lymphadenectomy. Furthermore, this benefit is observed in the N0 stage, but not observed in the N1 stage. In addition, the OS of patients receiving lymphadenectomy for four or more regions was significantly better than those receiving one to three regions lymphadenectomy. Age, the scope of regional lymphadenectomy, N stage, and tumor size were identified as prognostic factors. Conclusions: Extended cholecystectomy was not observed to significantly improve postoperative prognosis of patients with T2 GBC. However there was a significant survival benefit shown for those with regional lymphadenectomy, particularly for patients with negative lymph nodes. Future studies on the control of potential confounding factors and longer follow-ups are still needed.